Occurrence of the FBF7 fire blight resistance locus in accessions of apple wild species (Malus Mill.) - A. S. Lyzhin; N. N. Saveleva (Труды по прикладной ботанике, генетике и селекции, 2024)
Background. Fire blight (Erwinia amylovora (Burill) Winslow et al.) is a dangerous disease of fruit crops. In the Russian Federation, fire blight is one of the quarantine diseases. Apple resistance to fire blight is controlled polygenically. However, the data on the genotypes of Malus Mill. wild species and varieties in the context of individual resistance loci are scarce. The purpose of the research was studying the genetic collection of apple wild species according to the FBF7 fire blight resistance locus to identify promising sources of resistance to E. amylovora.Materials and methods. The materials of this study included 23 wild and two cultivated apple-tree species (50 accessions) from the genetic collection of the I.V. Michurin FSC. The FBF7 QTL for fire blight resistance was identified with the flanking SCAR-markers AE10-375 and GE-8019, and SSR-marker CH-F7-Fb1.Results and conclusion. The GE-8019 marker was identified in 50.0% of the apple accessions, AE10-375 in 76.0% of the accessions, and CH-F7-Fb1 in 30.0%. Inter- and intraspecific polymorphism of the Malus genus was revealed for the analyzed resistance locus, as well as for individual DNA markers linked to the FBF7 QTL. The GE-8019 and AE10-375 markers flanking the FBF7 QTL were found in 42.0% of the studied genotypes. Meanwhile, three diagnostic markers (GE-8019, AE10-375, and CH-F7-Fb1) were identified only in 7 accessions: M. × robusta var. persicifolia (Carr.) Rehd. (к-41279), M. × cerasifera var. hiemalis Spach. (к-2342) (Ser. Baccatae), M. sylvestris (L.) Mill. (k-73 and k-123), M. × spectabilis var. albi plena (Ait.) Borkh. (к-2416) (Ser. Malus), M. × sargentii (Rehd.) Langenf. (k-2428) (Ser. Toringonae), and M. coronaria (L.) Mill. (к-2336) (Ser. Coronariae). These forms are promising genetic sources of resistance to E. amylovora.